Comments on New Developments in the Law on Environmental Protection 2020 on Environmental Impact Assessment - Nguyet, Le Kim (VNU Journal of Science: Legal Studies; Vol 38 No 3DO - 10.25073/2588-1167/vnuls.4421, 2022)
With the process of international economic integration towards green growth and sustainable development in Vietnam, improving the legislation on environmental impact assessment plays an extremely important role. Environmental impact assessment activities have received more and more attention from the State, especially in the period of industrialization and modernization of the country. It can be seen that the legislation on environmental impact assessment in recent years has revealed many inadequacies in the process of law enforcement, and these are also the causes leading to the fact that many investment projects, when implemented in reality, do not meet the requirements for environmental protection, causing serious environmental pollution, greatly affecting public health, and sometimes getting out of control. In order to ensure socio-economic development without causing damage to the human living environment, Vietnam has been gradually approaching international experience in this field to gradually improve regulations on environmental impact assessment implementation process, environmental impact assessment scope definition, public consultation,... The Law on Environmental Protection 2020 consists of many new provisions which drastically reform the current environmental impact assessment process in Vietnam with the goal of improving the environment to ensure the public health and sustainable development.